COMPARISON OF GLYCATED HEMOGLOBIN AND GLYCATED ALBUMIN IN TYPE 2 DM PATIENTS WITH AND WITHOUT CAD - Andini Triasti Siregar; Nizam Zikri Akbar; Burhanuddin Nasution (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Diabetes has been associated with Coronary Artery Disease (CAD). The atherosclerosis, underlying the pathogenesis of CAD, has been activated since the early stages of hyperglycemia and accelerated with uncontrolled blood sugar level fluctuations. Therefore, sensitive glycemic markers are required to be used as a screening instrument such as a traditional glycated hemoglobin A1c (HbA1c) glycated hemoglobin marker and non-traditional Glycated Albumin (GA). This study was a cross-sectional conducted on May - July 2017 at the Adam Malik Hospital Medan. Subjects were patients with HbA1c> 7%, Hb> 10 g/dL and albumin> 3 g/dL, divided into DM+CAD and non-CAD DM groups. Sixty patients participated in this study consisting of 36 males (60%) and 24 females (40%), with a mean age of 56 years. There was a significant difference between HbA1c and GA between the non-CAD DM group and DM + CAD (p=0.001; 0.022.) Patient characteristics did not affect CAD complications in DM patients; a significant difference indicated that poor glycemic control increased the complication of CAD in patients with DM type 2. Glycated albumin examination is recommended for patients with type 2 diabetes with CAD.